Associations of Blood Pressure in Pregnancy With Offspring Blood Pressure Trajectories During Childhood and Adolescence: Findings From a Prospective Study. Issue 5 (May 2015) - Staley, James R.; Bradley, John; Silverwood, Richard J.; Howe, Laura D.; Tilling, Kate; Lawlor, Debbie A.; Macdonald‐Wallis, Corrie
Abstract : Background: Hypertensive disorders of pregnancy are related to higher offspring blood pressure (BP), but it is not known whether this association strengthens or weakens as BP changes across childhood. Our aim was to assess the associations of hypertensive disorders of pregnancy and maternal BP changes during pregnancy with trajectories of offspring BP from age 7 to 18 years. Methods and Results: In a large UK cohort of maternal–offspring pairs (N=6619), we used routine antenatal BP measurements to derive hypertensive disorders of pregnancy and maternal BP trajectories. These were related to offspring BP trajectories, obtained from research clinic assessments, using linear spline random‐effects models. After adjusting for maternal and offspring variables, including body mass index, offspring of women who had existing hypertension, gestational hypertension, or preeclampsia during pregnancy had on average higher BP at age 7 years compared to offspring of normotensive pregnancies (mean difference [95%CI] in systolic BP: 1.67 mm Hg [0.48, 2.86], 1.98 mm Hg [1.32, 2.65], and 1.22 mm Hg [−0.52, 2.97], respectively). These differences were consistent across childhood to age 18 years, as the patterns of BP change did not differ between offspring of hypertensive pregnancies and normotensive pregnancies. Maternal BP at 8 weeks' gestation was also positively associated with offspring BP in childhood and adolescence, but changes in BP across pregnancy were not strongly associated. Conclusions: The differences in BP between offspring of hypertensive pregnancies and offspring of normotensive pregnancies remain consistent across childhood and adolescence. These associations appear to be most contributed to by higher maternal BP in early pregnancy rather than by pregnancy‐related BP changes.